Effect Test Stimulant of Curcuma Rhizome Infusion (Curcuma xanthorrhiza Roxb.) On Male Mice Swiss Strain - Neni Lugki Nian Tary; Tanti Azizah Sujono (Universitas Muhammadiyah Surakarta, 2017)
The used of plants efficacious as medicines in the prevention of health problems had been known for along time the Indonesian people. The utilization of plants as medicine was based on the experience passeddown from generation to generation. The used of traditional medicines relatively favored by the people,the underlying factor are traditional medicines have less side effects than the modern medicines if usedappropriately. Curcuma (Curcuma xanthorrhiza Roxb.) used as refreshment which had stimulant effect..Stimulant was a substance that can stimulated the central nervous system which can speed up the processesin the body and minimize fatigue. Need to research the effects of stimulant infusion of curcuma rhizome.The research was conducted experimental methods pre-test and post-test. Twenty-five male mice Swissstrain used as experimental animals, which are divided into five groups, positive control (caffeine 100mg /kg BW), negative control (distilled water 0,5ml /20g BW), infusion of curcuma dose I (2.5 g/ kg BW), doseII (5g / kg BW), and dose III (10g / kg BW) respectively. Animal experiments tested using methods NatatoryExhaustion and treated with oral route. The effects of stimulant tired was calculated the time differencebefore and after treatment. The data obtained were analyzed non-parametric statistical tests, it’s KruskalWallis and Mann Whitney with a 95% confidence level. Infuse curcuma rhizome had the stimulant effect,the effect was obtained by increased the dose. At doses of 2.5 g / kg BW, 5g / kg BW, and 10 g / kg BW wasprovide a stimulant effect respectively by 2.82 minutes, 3.71 minutes and 4.94 minutes. Stimulant effect doseII and III had a greater effect than the positive control (p0,05), the dose I had similar effect compare withcontrol positive (p0,05).